Inverse Agonist of Retinoid-Related Orphan Receptor-Alpha Prevents Apoptosis and Degeneration in Nucleus Pulposus Cells via Upregulation of YAP - Tongzhou Liang; Jincheng Qiu; Shaoguang Li; Zhihuai Deng; Xianjian Qiu; Wenjun Hu; Pengfei Li; Taiqiu Chen; Zhancheng Liang; Hang Zhou; Bo Gao; Dongsheng Huang; et al. (Mediators of Inflammation)
Intervertebral disc degenerative disease (IDD) is the most common degenerative spine disease, which leads to chronic low back pain and symptoms in the lower extremities. In this study, we found that RORα, a member of the retinoid-related orphan receptor family, is significantly elevated in nucleus pulposus tissue in IDD patients. The elevation of RORα is associated with increased apoptosis of nucleus pulposus (NP) cells. Therefore, we applicated a well-established inverse agonist of RORα, SR3335, to investigate its role in regulating NP cell metabolism and apoptosis. To further investigate the mechanism that SR3335 regulates the pathogenesis of IDD in vitro, tumor necrosis factor alpha (TNF-α) stimulation was used in human NP cells to mimic the hostile environment that leads to degeneration. We found that SR3335 treatment reversed the trend of increased apoptosis in NP cells induced by TNF-α treatment. Next, TNF-α treatment upregulated the expression of type II collagen and aggrecan and downregulated MMP13 (matrix-degrading enzyme matrix metalloproteinase 13) and ADAMTS4 (a disintegrin and metalloproteinase with thrombospondin motifs 4). However, these effects were reversed after SR3335 treatment. Furthermore, we find that SR3335 mediated the effect in NP cells by regulating the YAP signaling pathway, especially by affecting the phosphorylation state of YAP. In conclusion, the reduction of matrix degradation enzymes and apoptosis upon SR3335 treatment suggests that SR3335 is a promising drug in reversing the deleterious microenvironment in IDD patients.